(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
This article presents the results of breeding studies of oil flax on rainfed areas. The results of a correlation analysis to identify the relationship between the elements of the structure of plants and the productivity of oil flax with the yield are presented. 2 varieties of oilseed flax with high yields have been identified.